Precision measurement of electrical charges in an optomechanical system beyond linearized dynamics - Xiong, Hao; Si, Liu-Gang; Wu, Ying (Applied physics letters, 2017)
Nonlinear interactions between cavity fields and mechanical oscillation in an optomechanical system coupled to a charged object are treated analytically, and the features of second-order sideband generation are discussed, which is beyond the conventional linearized description of optomechanical interactions. We show that resonantly enhanced feedback-backaction arising from radiation pressure can be substantively modified in the presence of electric interactions, which results in tunable optical nonlinearity and convenient optomechanical control. Especially, the system exhibits a remarkable electrical-charge dependent generation of the frequency component at the second-order sideband, which enables a potentially practical scheme for precision measurement of charges.